Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

In the preparation process of lithium manganese iron phosphate positive electrode material, heat treatment and non-aqueous solvent mixing technology are used to solve the problems of uneven distribution of lithium and phosphorus elements and poor carbon coating in the material, which significantly improves the charging and discharge performance and voltage platform of the battery.

CN119674038AActive Publication Date: 2025-03-21GUIZHOU ANDA TECH ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411955278.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have poor carbon coating properties and uneven distribution of lithium and phosphorus elements, resulting in poor charging and discharging performance and voltage platform of the battery.

Method used

By performing heat treatment under a protective atmosphere, a ferromanganese oxide doped with M elements was obtained, and mixed with a lithium source, a phosphorus source and a carbon source in a non-aqueous solvent. After grinding and drying, a second heat treatment was performed to prepare a lithium ferromanganese phosphate positive electrode material. This method avoids segregation of oxalic acid gas production and lithium and phosphorus sources, ensuring uniformity of element distribution and good carbon coating.

Benefits of technology

The uniform distribution of lithium and phosphorus elements and the improvement of carbon coating in lithium manganese iron phosphate positive electrode material are achieved, and the battery produced has excellent charging and discharging performance and voltage platform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674038A_ABST
    Figure CN119674038A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium batteries, and discloses a lithium manganese iron phosphate positive electrode material and a preparation method and application thereof, and the expression of the positive electrode material is Lii (FexMyMnz) PO4 / C, wherein x is more than or equal to 0.15 and less than or equal to 0.45, 0 lt; y < = 0.03, 0.52 < = z < = 0.85, and 0.98 < = i < = 1.05; m is selected from at least one of Mg, Ti, V, Ni, Zn, Cu, Zr and Nb; the variable coefficient of the phosphorus element content in the positive electrode material is less than or equal to 0.045. The lithium manganese iron phosphate positive electrode material provided by the invention is good in carbon coating property and uniform in phosphorus element distribution, and the prepared battery has good electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, lithium iron phosphate, as a positive electrode material for lithium-ion batteries, has been widely used in the field of power batteries due to its high safety, low cost and good cycle performance. However, its lower voltage platform (3.4V) makes its energy density low and cannot meet the market demand for long-range power batteries.

[0003] Lithium manganese iron phosphate is a new type of phosphate lithium-ion battery cathode material formed by replacing a certain proportion of iron in lithium iron phosphate with manganese. It has the same structure as lithium iron phosphate, but has a higher voltage platform (4.1V) and higher energy density, which is theoretically 20% higher than lithium iron phosphate under the same conditions. Its production process can achieve a large degree of compatibility with lithium iron phosphate, and its production cost is low and close to that of lithium iron phosphate, so it has attracted widespread attention in the market.

[0004] At present, the main methods for preparing lithium manganese iron phosphate are solid phase method and hydrothermal method. The hydrothermal method for synthesizing lithium manganese iron phosphate needs to be carried out in a high temperature and high pressure environment, which has high requirements for equipment and high cost for industrial application. At present, the solid phase method for synthesizing lithium manganese iron phosphate mainly prepares the manganese source, iron source, phosphorus source, lithium source and carbon source through premixing, sand milling, spray drying and sintering. However, this simple mixing cannot achieve uniform mixing of manganese and iron at the atomic level, and the prepared lithium manganese iron phosphate has poor charge and discharge capacity and constant voltage platform.

[0005] In order to improve the problem of uniform distribution of ferromanganese, the current solution is to obtain ferromanganese salts by coprecipitation, such as ferromanganese phosphate, ferromanganese oxalate, etc. In the above process, due to the release of oxalate and crystal water, the carbon coating of lithium manganese iron phosphate is poor, and phosphorus segregation causes the obtained lithium manganese iron phosphate to have poor electrical performance. Summary of the invention

[0006] In order to overcome the problems of poor carbon coating and lithium and phosphorus segregation in the lithium iron phosphate positive electrode material provided by the prior art, a lithium iron phosphate positive electrode material and a preparation method and application thereof are provided. The lithium iron phosphate positive electrode material has good carbon coating and uniform distribution of phosphorus element, and the prepared battery has good electrical properties.

[0007] In order to achieve the above-mentioned object, the present invention provides a lithium manganese iron phosphate positive electrode material in the first aspect, wherein the positive electrode material is expressed as Li i (Fe x M y Mn z )PO 4 / C; Among them, 0.15≤x≤0.45, 0 <y≤0.03,0.52≤z≤0.85,0.98≤i≤1.05; M is selected from at least one of Mg, Ti, V, Ni, Zn, Cu, Zr and Nb; The coefficient of variation of the phosphorus content in the positive electrode material is ≤0.045.

[0008] The second aspect of the present invention provides a method for preparing the positive electrode material provided by the first aspect of the present invention, the method comprising the following steps: (1) in the presence of a first solvent, a manganese source, an iron source and an M source are mixed to obtain a mixed solution, and then mixed with oxalic acid and / or oxalate to separate a precipitate; (2) subjecting the precipitate to a first heat treatment under a protective atmosphere to obtain manganese iron oxide doped with the M element; (3) in the presence of a second non-aqueous solvent, mixing the manganese iron oxide with a lithium source, a phosphorus source and a carbon source to obtain a slurry, and grinding and drying the slurry to obtain a positive electrode material precursor; (4) Under a protective atmosphere, subjecting the cathode material precursor to a second heat treatment to obtain a lithium manganese iron phosphate cathode material.

[0009] The third aspect of the present invention provides an application of the positive electrode material provided by the first aspect of the present invention or the positive electrode material prepared by the method provided by the second aspect of the present invention in a battery.

[0010] The beneficial technical effects of the present invention are: (1) The elements in the positive electrode material provided by the present invention, especially lithium and phosphorus, are evenly distributed, and the carbon coating is good. The manufactured battery has excellent charge and discharge performance and voltage platform.

[0011] (2) The method for preparing lithium manganese iron phosphate positive electrode material provided by the present invention uses oxalic acid (salt) as a precipitant to co-precipitate a manganese source, an iron source and an M source, and heat-treats the precipitate to obtain a manganese iron oxide with uniform distribution of metal elements; then, the manganese iron oxide is ground and mixed with a lithium source, a phosphorus source and a carbon source in a non-aqueous solvent to obtain a positive electrode material precursor, and heat-treats the precursor to avoid oxalic acid gas production and segregation of the lithium source and the phosphorus source, so that the elements, especially the lithium element and the phosphorus element, are evenly distributed, and the carbon coating is good.

[0012] Furthermore, by adding an antioxidant, the valence change of manganese and iron can be avoided during the preparation of the positive electrode material, and the generation of trivalent manganese and iron can be reduced, thereby further improving the charge and discharge performance of the battery made of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1This is the XRD spectrum of the manganese iron oxide obtained in Example 1 of the present invention; Figure 2 This is a SEM image of the ferromanganese oxide obtained in Example 1 of the present invention; Figure 3 This is the XRD spectrum of the lithium manganese iron phosphate positive electrode material obtained in Example 1 of the present invention; Figure 4 This is a SEM image of the lithium manganese iron phosphate positive electrode material obtained in Example 1 of the present invention; Figure 5 This is a SEM image of the lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1 of the present invention; Figure 6 This is an EDS line scan of the phosphorus element in the lithium manganese iron phosphate positive electrode material obtained in Example 1 of the present invention; Figure 7 This is an EDS line scan of the phosphorus element in the lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] The first aspect of the present invention provides a lithium manganese iron phosphate positive electrode material, the positive electrode material is expressed as Li i (Fe x M y Mn z )PO 4 / C; Among them, 0.15≤x≤0.45, 0 <y≤0.03,0.52≤z≤0.85,0.98≤i≤1.05; M is selected from at least one of Mg, Ti, V, Ni, Zn, Cu, Zr and Nb; The coefficient of variation of the phosphorus content in the positive electrode material is ≤0.045.

[0016] In the present invention, the values ​​of x, y, z, and i can be measured by inductively coupled plasma elemental analysis (ICP).

[0017] The X-ray energy dispersive spectrometry (EDS) signal intensity of phosphorus elements at different positions in the positive electrode material is X i , X iThe average value is μ, the standard deviation is σ, the coefficient of variation of the EDS signal intensity of the phosphorus element in the positive electrode material is CV=σ / μ, and the coefficient of variation of the EDS signal intensity of the phosphorus element is used to represent the coefficient of variation of the phosphorus element content.

[0018] The elements, especially the phosphorus element, in the lithium manganese iron phosphate positive electrode material provided by the present invention are evenly distributed, and the carbon coating is good, so the prepared battery has excellent charge and discharge performance and voltage platform.

[0019] According to a preferred embodiment of the present invention, 0.15≤x≤0.35, 0 <y≤0.02,0.63≤z≤0.85,1≤i≤1.02。

[0020] In the present invention, when the composition of the positive electrode material is within the above range, the charge and discharge performance and voltage platform of the prepared battery can be further improved.

[0021] According to the present invention, preferably, M is selected from at least one of Mg, Ti, Ni and Zn.

[0022] In the present invention, the M element can further improve the charge and discharge performance of the battery made of the positive electrode material.

[0023] According to the present invention, preferably, the coefficient of variation of the phosphorus content in the positive electrode material is ≤0.035%.

[0024] In the present invention, when the coefficient of variation of the phosphorus content is within the above range, the charge and discharge performance of the positive electrode material can be further improved.

[0025] According to a preferred embodiment of the present invention, the carbon content in the positive electrode material is 1.4-2.5wt%.

[0026] In the present invention, when the carbon content in the positive electrode material is within the above range, the conductivity of the material can be further improved.

[0027] More preferably, the carbon content is 1.5-1.9wt%.

[0028] According to the present invention, preferably, the median particle size of the positive electrode material is 50-600 nm.

[0029] In the present invention, when the median particle size of the positive electrode material is within the above range, the compaction density of the positive electrode material can be further increased, thereby improving the conductivity.

[0030] More preferably, the median particle size of the positive electrode material is 50-250 nm.

[0031] The second aspect of the present invention provides a method for preparing the positive electrode material provided by the first aspect of the present invention, the method comprising the following steps: (1) in the presence of a first solvent, a manganese source, an iron source and an M source are mixed to obtain a mixed solution, and then mixed with oxalic acid and / or oxalate to separate a precipitate; (2) subjecting the precipitate to a first heat treatment under a protective atmosphere to obtain manganese iron oxide doped with the M element; (3) in the presence of a second non-aqueous solvent, mixing the manganese iron oxide with a lithium source, a phosphorus source and a carbon source to obtain a slurry, and grinding and drying the slurry to obtain a positive electrode material precursor; (4) Under a protective atmosphere, subjecting the cathode material precursor to a second heat treatment to obtain a lithium manganese iron phosphate cathode material.

[0032] The invention provides a method for preparing a lithium manganese iron phosphate positive electrode material. The method comprises the following steps: using oxalic acid (salt) as a precipitant, co-precipitating a manganese source, an iron source and an M source, and heat-treating the precipitate to obtain a manganese iron oxide doped with the M element and having a uniform distribution of metal elements; and then grinding and mixing the manganese iron oxide with a lithium source, a phosphorus source and a carbon source in a non-aqueous solvent to obtain a positive electrode material precursor. When heat-treating the precursor, gas production by oxalic acid and segregation of the lithium source and the phosphorus source can be avoided. The elements in the obtained positive electrode material, especially lithium and phosphorus elements, are uniformly distributed, and the carbon coating is good. The manufactured battery has excellent charge and discharge performance and voltage platform.

[0033] The present invention has no particular limitation on the protective atmosphere, and the protective atmosphere may be nitrogen and / or argon.

[0034] The present invention has no particular limitation on the manganese source, iron source and M source, and those skilled in the art can select them conventionally. According to a specific embodiment of the present invention, the manganese source is selected from at least one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate.

[0035] The iron source is selected from at least one of ferrous sulfate, ferrous chloride and ferrous acetate.

[0036] The M source is selected from soluble salts of M, such as soluble nitrates, sulfates and acetates.

[0037] The present invention has no particular limitation on the specific type of the oxalate, but ammonium oxalate is preferred.

[0038] The present invention does not particularly limit the specific amount of oxalic acid and / or oxalate, and those skilled in the art can routinely select the amount that can fully precipitate metal ions. According to a specific embodiment of the present invention, the molar ratio of the total amount of metal elements in the manganese source, the iron source and the M source to the oxalic acid (salt) calculated as oxalate is 1:1-1.05.

[0039] According to the present invention, preferably, the total concentration of metal ions in the mixed solution is 0.2-2 mol / L.

[0040] In the present invention, when the total concentration of metal ions in the mixed solution is within the above range, the metal ions can be precipitated more uniformly.

[0041] More preferably, the total concentration of metal ions in the mixed solution is 0.2-1 mol / L.

[0042] According to the present invention, preferably, the mixed solution further comprises an antioxidant.

[0043] In the present invention, by adding an antioxidant, the valence change of manganese and iron can be avoided during the preparation of the positive electrode material, and the generation of trivalent manganese and iron can be reduced, thereby further improving the charge and discharge performance of the battery made of the positive electrode material.

[0044] The present invention has no particular limitation on the specific type and amount of the antioxidant, and those skilled in the art can make routine selections.

[0045] According to a specific embodiment of the present invention, the antioxidant is selected from at least one of ascorbic acid, citric acid and tartaric acid.

[0046] The dosage of the antioxidant is 0.1-0.4% of the total mass of the manganese source and the iron source.

[0047] In the present invention, the ferromanganese oxalate may be first dried before the first heat treatment. According to a specific embodiment of the present invention, the first drying method is to heat to 90-120° C. under a protective atmosphere and keep the temperature for 2-4 hours.

[0048] According to a preferred embodiment of the present invention, the temperature of the first heat treatment is 500-700° C., and the time is 5-12 hours.

[0049] In the present invention, when the conditions of the first heat treatment are within the above range, ferromanganese oxalate can be fully converted into ferromanganese oxide, while avoiding the degradation of the performance of the positive electrode material due to particle aggregation.

[0050] More preferably, the temperature of the first heat treatment is 550-600° C., and the time is 8-10 h.

[0051] The present invention does not particularly limit the specific types of the lithium source, phosphorus source and carbon source, and those skilled in the art can routinely select. According to a specific embodiment of the present invention, the lithium source is selected from at least one of lithium oxalate, lithium hydroxide, lithium carbonate, lithium acetate and lithium dihydrogen phosphate.

[0052] The phosphorus source is selected from at least one of ammonium dihydrogen phosphate, phosphoric acid and lithium dihydrogen phosphate.

[0053] The carbon source is selected from at least one of glucose, galactose, lactose, sucrose, caramel, phenolic resin, polyethylene glycol and polyvinyl alcohol.

[0054] The specific type of the solvent is not particularly limited in the present invention, and can be conventionally selected by a person skilled in the art. According to a specific embodiment of the present invention, the first solvent is water.

[0055] The second non-aqueous solvent is N-methylpyrrolidone and / or anhydrous ethanol.

[0056] According to a preferred embodiment of the present invention, in step (1), the molar ratio of the manganese source, the iron source and the M source, calculated as metal elements, satisfies n(Mn):n(Fe):n(M)=1-1.2:0.4-1:0.015-0.045.

[0057] In the present invention, when the molar ratio of the manganese source, the iron source and the M source satisfies the above range, the electrical performance of the battery can be further improved.

[0058] More preferably, the molar ratio of the manganese source, iron source and M source satisfies n(Mn):n(Fe):n(M)=1.05-1.15:0.5-0.9:0.02-0.03.

[0059] According to the present invention, preferably, in step (3), the molar ratio of the manganese iron oxide to the lithium source, the phosphorus source and the carbon source, calculated on the basis of metal elements, phosphorus elements and carbon elements, satisfies n(Li):n(Mn+Fe):n(P):n(C)=0.98-1.05:0.96-1:0.98-1.05:0.7-1.3.

[0060] In the present invention, when the molar ratio of the manganese iron oxide to the lithium source, the phosphorus source and the carbon source satisfies the above range, the electrical performance of the battery can be further improved.

[0061] More preferably, the molar ratio of the manganese iron oxide to the lithium source, the phosphorus source and the carbon source satisfies n(Li):n(Mn+Fe):n(P):n(C)=1-1.02:0.98-1:1-1.05:0.8-1.

[0062] The present invention has no particular limitation on the solid content of the slurry, and those skilled in the art can make a conventional selection. According to a specific embodiment of the present invention, the solid content of the slurry is 20-70wt%, more specifically 37-50wt%.

[0063] The present invention does not particularly limit the specific method of grinding, and those skilled in the art can routinely select, for example, ball milling or rod milling.

[0064] According to the present invention, preferably, the median particle size of the positive electrode material precursor is 100-200 nm.

[0065] In the present invention, when the median particle size of the cathode material precursor is within the above range, the uniformity of the slurry and the crystallinity of the cathode material can be further improved.

[0066] More preferably, the median particle size of the positive electrode material precursor is 120-180 nm.

[0067] According to a preferred embodiment of the present invention, the temperature of the second heat treatment is 220-800° C., and the time is 4-12 hours.

[0068] More preferably, the second heat treatment adopts a programmed temperature method: (1) Raise the temperature to 220-350℃ at a rate of 1-5℃ / min and keep warm for 2-3h; (2) Continue heating to 450-650℃ at a rate of 1.5-2.5℃ / min and keep warm for 4-5h; (3) Continue to increase the temperature to 650-800℃ at a rate of 1-1.5℃ / min and keep it at this temperature for 7-12h.

[0069] In the present invention, the second heat treatment adopts a programmed temperature method, which can further improve the crystallinity of the positive electrode material.

[0070] In the present invention, the slurry may be subjected to a second drying process before the second heat treatment. Preferably, the second drying process is spray drying, with an inlet temperature of 300-400°C and an outlet temperature of 180-220°C.

[0071] The third aspect of the present invention provides an application of the positive electrode material provided by the first aspect of the present invention or the positive electrode material prepared by the method provided by the second aspect of the present invention in a battery.

[0072] The present invention will be described in detail below through examples.

[0073] In the following examples, the contents of various elements (except carbon) in ferromanganese oxalate, ferromanganese oxide and positive electrode materials were determined by inductively coupled plasma elemental analysis (ICP); The valence states of manganese and iron were determined by X-ray diffraction (XRD); The hydration number of ferromanganese oxalate was determined by thermogravimetric analysis; The carbon content in the positive electrode material is measured by a carbon-sulfur tester.

[0074] The particle size is measured with a laser particle size analyzer in accordance with GB / T 19077-2016. The phosphorus content at different positions of the positive electrode material was determined by X-ray energy dispersive spectroscopy (EDS) line scanning.

[0075] Unless otherwise specified, all reagents and raw materials were purchased from commercial sources.

[0076] Example 1 (1) Weigh 19.601 kg of manganese sulfate monohydrate (purity 99.4 wt%, the same below), 11.716 kg of battery-grade ferrous sulfate heptahydrate (purity 99.2 wt%, the same below), 180.19 g of magnesium sulfate, 165.31 g of titanyl sulfate, 71.86 g of zinc sulfate, 300 kg of pure water, and 95.07 g of ascorbic acid, raise the temperature and maintain it at 40°C, introduce nitrogen as a protective gas, and stir to obtain a mixed solution. Weigh 18.945 kg of battery-grade ammonium oxalate and 200 kg of pure water, then add them to the above mixed solution, perform a coprecipitation reaction at 40°C, and obtain manganese iron oxalate with doped elements after washing and drying.

[0077] The chemical composition of the above ferromanganese oxalate is Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 C 2 O 4 ·2H 2 O.

[0078] (2) The above-mentioned ferromanganese oxalate was placed in a graphite box, transferred to a box furnace filled with nitrogen, and heated to 150°C at a rate of 5°C / min and kept at this temperature for 3 hours to remove crystal water. The temperature was then raised to 550°C at a rate of 3°C / min and kept at this temperature for 10 hours to obtain ferromanganese oxide with doped elements.

[0079] The chemical composition of the above-mentioned ferromanganese oxide is (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 )O.

[0080] (3) Weigh 237.639 g of the above-mentioned manganese iron oxide powder, add 615.867 g of N-methylpyrrolidone, and add 310.052 g of battery-grade lithium dihydrogen phosphate, 2.222 g of lithium carbonate, and 65.954 g of polyethylene glycol under stirring to obtain a positive electrode material precursor slurry. The solid content of the slurry is calculated to be 50 wt% by the amount of material added.

[0081] The slurry was sand-milled with an organic sand mill, and the median particle size of the particles in the sand-milled slurry was measured by a laser particle size analyzer to be 136 nm.

[0082] The slurry was spray dried with an inlet temperature of 380° C. and an outlet temperature of 200° C. to obtain a positive electrode material precursor.

[0083] (4) The above cathode material precursor is transferred into an atmosphere furnace, and under a nitrogen protective atmosphere, the temperature is first increased from room temperature to 350°C at a rate of 2°C / min, kept at this temperature for 3 h, then increased to 600°C at a rate of 1.5°C / min, kept at this temperature for 4 h, and then increased to 700°C at a rate of 1°C / min, kept at this temperature for 10 h, and then naturally cooled and crushed to obtain lithium manganese iron phosphate cathode material.

[0084] The chemical composition of the positive electrode material is Li 1.01 (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 )PO 4 / C, with a carbon content of 1.85wt%.

[0085] Example 2 (1) Weigh 14.844 kg of battery-grade manganese sulfate monohydrate, 11.009 kg of battery-grade ferrous sulfate heptahydrate, 145.99 g of magnesium sulfate, 133.94 g of titanyl sulfate, 58.22 g of zinc sulfate, 300 kg of purified water, and 76.750 g of ascorbic acid, raise the temperature and maintain it at 40°C, introduce nitrogen as a protective gas, and stir to obtain a mixed solution. Weigh 15.350 kg of battery-grade ammonium oxalate and 200 kg of purified water, mix them, and then add them to the above mixed solution to perform a coprecipitation reaction. After washing and drying, manganese iron oxalate with doped elements is obtained.

[0086] The chemical composition of the above ferromanganese oxalate is Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.33 Mn 0.65 C 2 O 4 ·2H 2 O.

[0087] (2) The above-mentioned ferromanganese oxalate was placed in a graphite box, transferred to a box furnace filled with nitrogen, and heated to 150°C at a rate of 5°C / min and kept at this temperature for 3 hours to remove crystal water. The temperature was then raised to 550°C at a rate of 3°C / min and kept at this temperature for 10 hours to obtain ferromanganese oxide with doped elements.

[0088] The chemical composition of the above-mentioned ferromanganese oxide is (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.33 Mn 0.65 )O.

[0089] (3) Weigh 253.482 g of the above-mentioned manganese iron oxide powder, add 659.258 g of N-methylpyrrolidone, and add 333.055 g of battery-grade lithium dihydrogen phosphate, 2.37 g of lithium carbonate, and 70.351 g of polyethylene glycol under stirring to obtain a positive electrode material precursor slurry. The solid content of the slurry is calculated to be 50 wt% by the amount of material added.

[0090] The slurry was sand-milled with an organic sand mill, and the median particle size of the particles in the sand-milled slurry was measured by a laser particle size analyzer to be 169 nm.

[0091] The slurry was spray dried with an inlet temperature of 380° C. and an outlet temperature of 200° C. to obtain a positive electrode material precursor.

[0092] (4) The above cathode material precursor is transferred into an atmosphere furnace, and under a nitrogen protective atmosphere, the temperature is first increased from room temperature to 350°C at a rate of 2°C / min, kept at this temperature for 3 h, then increased to 600°C at a rate of 1.5°C / min, kept at this temperature for 4 h, and then increased to 700°C at a rate of 1°C / min, kept at this temperature for 10 h, and then naturally cooled and crushed to obtain lithium manganese iron phosphate cathode material.

[0093] The chemical composition of the positive electrode material is Li 1.01 (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.33 Mn 0.65 )PO 4 / C, with a carbon content of 1.79wt%.

[0094] Example 3 (1) Weigh 18.650 kg of battery-grade manganese sulfate monohydrate, 11.120 kg of battery-grade ferrous sulfate heptahydrate, 253.55 g of magnesium sulfate, 114.20 g of zinc sulfate, 300 kg of purified water, and 90.858 g of ascorbic acid, raise the temperature and maintain it at 40°C, introduce nitrogen as a protective gas, and stir to obtain a mixed solution. Weigh 18.013 kg of battery-grade ammonium oxalate and 200 kg of purified water, then add them to the mixed solution to perform a coprecipitation reaction, and obtain ferromanganese oxalate with doped elements after washing and drying.

[0095] The chemical composition of the above ferromanganese oxalate is Mg 0.015 Zn 0.005 Fe 0.28 Mn 0.7 C 2 O 4 ·2H 2 O.

[0096] (2) The above-mentioned ferromanganese oxalate was placed in a graphite box, transferred to a box furnace filled with nitrogen, and heated to 150°C at a rate of 5°C / min and kept at this temperature for 3 hours to remove crystal water. The temperature was then raised to 550°C at a rate of 3°C / min and kept at this temperature for 10 hours to obtain ferromanganese oxide with doped elements.

[0097] The chemical composition of the above-mentioned ferromanganese oxide is (Mg 0.015 Zn 0.005 Fe 0.28 Mn 0.7 )O.

[0098] (3) Weigh 238.809 g of the above-mentioned manganese iron oxide powder, add 743.013 g of N-methylpyrrolidone, and add 318.123 g of battery-grade lithium dihydrogen phosphate, 2.222 g of lithium carbonate, and 66.218 g of polyethylene glycol under stirring to obtain a positive electrode material precursor slurry. The solid content of the slurry is calculated to be 50 wt% by the amount of material added.

[0099] The slurry was sand-milled with an organic sand mill, and the median particle size of the particles in the sand-milled slurry was measured by a laser particle size analyzer to be 179 nm.

[0100] The slurry was spray dried with an inlet temperature of 380° C. and an outlet temperature of 200° C. to obtain a positive electrode material precursor.

[0101] (4) The above cathode material precursor is transferred into an atmosphere furnace, and under a nitrogen protective atmosphere, the temperature is first increased from room temperature to 350°C at a rate of 2°C / min, kept at this temperature for 3 h, then increased to 600°C at a rate of 1.5°C / min, kept at this temperature for 4 h, and then increased to 700°C at a rate of 1°C / min, kept at this temperature for 10 h, and then naturally cooled and crushed to obtain lithium manganese iron phosphate cathode material.

[0102] The chemical composition of the above positive electrode material is Li 1.01 (Mg 0.015 Zn 0.005 Fe 0.28 Mn 0.7 )PO 4 / C, with a carbon content of 1.81wt%.

[0103] Example 4 (1) Weigh 19.410 kg of battery-grade manganese sulfate monohydrate, 11.597 kg of battery-grade ferrous sulfate heptahydrate, 350.75 g of titanyl sulfate, 118.93 g of zinc sulfate, 300 kg of purified water, and 95.937 g of ascorbic acid, raise the temperature and maintain it at 40°C, introduce nitrogen as a protective gas, and stir to obtain a mixed solution. Weigh 19.187 kg of battery-grade ammonium oxalate and 200 kg of purified water, mix them, and then add them to the above mixed solution to perform a coprecipitation reaction. After washing and drying, manganese iron oxalate with doped elements is obtained.

[0104] The chemical composition of the above ferromanganese oxalate is Ti 0.015 Zn 0.005 Fe 0.28 Mn 0.7 C 2 O 4 ·2H 2 O.

[0105] (2) The above-mentioned ferromanganese oxalate was placed in a graphite box, transferred to a box furnace filled with nitrogen, and heated to 150°C at a rate of 5°C / min and kept at this temperature for 3 hours to remove crystal water. The temperature was then raised to 550°C at a rate of 3°C / min and kept at this temperature for 10 hours to obtain ferromanganese oxide with doped elements.

[0106] The chemical composition of the above-mentioned manganese iron oxide is (Ti 0.015 Zn 0.005 Fe 0.28 Mn 0.7 )O.

[0107] (3) Weigh 316.492 g of the above-mentioned manganese iron oxide powder, add 818.646 g of N-methylpyrrolidone, and add 411.823 g of battery-grade lithium dihydrogen phosphate, 2.933 g of lithium carbonate, and 87.398 g of polyethylene glycol under stirring to obtain a positive electrode material precursor slurry. The solid content of the slurry is calculated to be 50 wt% by the amount of material added.

[0108] The slurry was sand-milled with an organic sand mill, and the median particle size of the particles in the sand-milled slurry was measured by a laser particle size analyzer to be 147 nm.

[0109] The slurry was spray dried with an inlet temperature of 380° C. and an outlet temperature of 200° C. to obtain a positive electrode material precursor.

[0110] (4) The above cathode material precursor is transferred into an atmosphere furnace, and under a nitrogen protective atmosphere, the temperature is first increased from room temperature to 350°C at a rate of 2°C / min, kept at this temperature for 3 h, then increased to 600°C at a rate of 1.5°C / min, kept at this temperature for 4 h, and then increased to 700°C at a rate of 1°C / min, kept at this temperature for 10 h, and then naturally cooled and crushed to obtain lithium manganese iron phosphate cathode material.

[0111] The chemical composition of the above positive electrode material is Li 1.01 (Ti 0.015 Zn 0.005 Fe 0.28 Mn 0.7 )PO 4 / C, of ​​which the carbon content is 1.93wt%.

[0112] Comparative Example 1 (1) Weigh 19.791 kg of battery-grade manganese sulfate monohydrate, 11.835 kg of battery-grade ferrous sulfate heptahydrate, 181.96 g of magnesium sulfate, 166.94 g of titanyl sulfate, 72.57 g of zinc sulfate, 300 kg of purified water, and 96.963 g of ascorbic acid, raise the temperature and maintain it at 40°C, introduce nitrogen as a protective gas, and stir to obtain a mixed solution. Weigh 19.132 kg of battery-grade ammonium oxalate and 200 kg of purified water, mix them, and then add them to the above mixed solution to perform a coprecipitation reaction, and obtain ferromanganese oxalate after washing and drying.

[0113] The chemical composition of the above ferromanganese oxalate is Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 C 2 O 4 ·2H 2 O.

[0114] (2) The above-mentioned ferromanganese oxalate was placed in a graphite box, transferred to a box furnace filled with nitrogen, and heated to 150°C at a rate of 5°C / min and kept at this temperature for 3 hours to remove crystal water. The temperature was then raised to 550°C at a rate of 3°C / min and kept at this temperature for 10 hours to obtain ferromanganese oxide with doped elements.

[0115] The chemical composition of the above-mentioned ferromanganese oxide is (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 )O.

[0116] (3) Weigh 1792.507 g of the above-mentioned ferromanganese oxalate, add 2866.091 g of water, and add 1042.925 g of battery-grade lithium dihydrogen phosphate, 11.851 g of lithium carbonate, and 341.674 g of polyethylene glycol under stirring to obtain a positive electrode material precursor slurry. The solid content of the slurry is calculated to be 50 wt% by the amount of material added.

[0117] The slurry was sand-milled with an organic sand mill, and the median particle size of the particles in the sand-milled slurry was measured by a laser particle size analyzer to be 208 nm.

[0118] The slurry was spray dried with an inlet temperature of 210° C. and an outlet temperature of 95° C. to obtain a positive electrode material precursor.

[0119] (4) The above cathode material precursor is transferred into an atmosphere furnace, and under a nitrogen protective atmosphere, the temperature is first increased from room temperature to 350°C at a rate of 2°C / min, kept at this temperature for 3 h, then increased to 600°C at a rate of 1.5°C / min, kept at this temperature for 4 h, and then increased to 700°C at a rate of 1°C / min, kept at this temperature for 10 h, and then naturally cooled and crushed to obtain lithium manganese iron phosphate cathode material.

[0120] The chemical composition of the above positive electrode material is Li 1.01 (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 )PO 4 / C, of ​​which the carbon content is 1.76wt%.

[0121] Comparative Example 2 (1) Weigh 18.840 kg of battery-grade manganese sulfate monohydrate, 11.796 kg of battery-grade ferrous sulfate heptahydrate, 300 kg of purified water, and 91.473 g of ascorbic acid, raise the temperature and maintain it at 40°C, introduce nitrogen as a protective gas, and stir to obtain a mixed solution. Weigh 18.460 kg of battery-grade ammonium oxalate and 200 kg of purified water, then add them to the mixed solution to perform a coprecipitation reaction, and obtain ferromanganese oxalate after washing and drying.

[0122] The chemical composition of the above ferromanganese oxalate is Fe 0.3 Mn 0.7 C 2 O 4 ·2H 2 O.

[0123] (2) The above-mentioned ferromanganese oxalate was placed in a graphite box, transferred to a box furnace filled with nitrogen, and heated to 150°C at a rate of 5°C / min and kept at this temperature for 3 h to remove crystal water, and then heated to 550°C at a rate of 3°C / min and kept at this temperature for 10 h to obtain ferromanganese oxide.

[0124] The chemical composition of the above-mentioned manganese iron oxide is (Fe 0.3 Mn 0.7 )O.

[0125] (3) Weigh 316.840 g of the above-mentioned manganese iron oxide powder, add 823.726 g of N-methylpyrrolidone, and add 415.983 g of battery-grade lithium dihydrogen phosphate, 2.963 g of lithium carbonate, and 87.94 g of polyethylene glycol under stirring to obtain a positive electrode material precursor slurry. The solid content of the slurry is calculated to be 50 wt% by the amount of material added.

[0126] The slurry was sand-milled with an organic sand mill, and the median particle size of the particles in the sand-milled slurry was measured by a laser particle size analyzer to be 195 nm.

[0127] The slurry was spray dried with an inlet temperature of 380° C. and an outlet temperature of 200° C. to obtain a positive electrode material precursor.

[0128] (4) The above cathode material precursor is transferred into an atmosphere furnace, and under a nitrogen protective atmosphere, the temperature is first increased from room temperature to 350°C at a rate of 2°C / min, kept at this temperature for 3 h, then increased to 600°C at a rate of 1.5°C / min, kept at this temperature for 4 h, and then increased to 700°C at a rate of 1°C / min, kept at this temperature for 10 h, and then naturally cooled and crushed to obtain lithium manganese iron phosphate cathode material.

[0129] The chemical composition of the positive electrode material is Li 1.01 (Fe 0.3 Mn 0.7 )PO 4 / C, with a carbon content of 1.71wt%.

[0130] Comparative Example 3 (1) Weigh 13.321 kg of battery-grade manganese sulfate monohydrate, 7.784 kg of battery-grade ferrous sulfate heptahydrate, 121.66 g of magnesium sulfate, 112.55 g of titanyl sulfate, 48.52 g of zinc sulfate, and 300 kg of purified water, heat and maintain the temperature at 40°C, and stir to obtain a mixed solution. Weigh 9.884 kg of 17.2 wt% ammonia water, and then add it to the mixed solution to perform a coprecipitation reaction, and wash and dry to obtain ferromanganese hydroxide with doped elements.

[0131] The chemical composition of the above-mentioned ferromanganese oxyhydroxide is (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 )OOH.

[0132] (2) The above-mentioned ferromanganese hydroxide is placed in a graphite box, transferred to a box furnace filled with nitrogen, and first heated to 150°C at a rate of 5°C / min and kept at this temperature for 3 hours to remove crystal water, and then heated to 550°C at a rate of 3°C / min and kept at this temperature for 10 hours to obtain ferromanganese oxide with doped elements.

[0133] The chemical composition of the above-mentioned ferromanganese oxide is (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 )O.

[0134] (3) Weigh 237.639 g of the above-mentioned manganese iron oxide powder, add 659.046 g of N-methylpyrrolidone, and add 310.052 g of battery-grade lithium dihydrogen phosphate, 2.222 g of lithium carbonate, and 65.94 g of polyethylene glycol under stirring to obtain a positive electrode material precursor slurry. The solid content of the slurry is calculated to be 50 wt% by the amount of material added.

[0135] The slurry was sand-milled with an organic sand mill, and the median particle size of the particles in the sand-milled slurry was measured by a laser particle size analyzer to be 187 nm.

[0136] The slurry was spray dried with an inlet temperature of 380° C. and an outlet temperature of 200° C. to obtain a positive electrode material precursor.

[0137] (4) The above cathode material precursor is transferred into an atmosphere furnace, and under a nitrogen protective atmosphere, the temperature is first increased from room temperature to 350°C at a rate of 2°C / min, kept at this temperature for 3 h, then increased to 600°C at a rate of 1.5°C / min, kept at this temperature for 4 h, and then increased to 700°C at a rate of 1°C / min, kept at this temperature for 10 h, and then naturally cooled and crushed to obtain lithium manganese iron phosphate cathode material.

[0138] The chemical composition of the positive electrode material is Li 1.01 (Mg 0.01 Ti 0.007 Zn 0.003 Fe 0.28 Mn 0.7 )PO 4 / C, with a carbon content of 1.87wt%.

[0139] Test Example 1 The manganese iron oxide and the positive electrode material obtained in Example 1 and Comparative Example 1 were characterized by XRD and SEM.

[0140] Figure 1 , Figure 2 They are the XRD spectrum and SEM image of the manganese iron oxide obtained in Example 1.

[0141] pass Figure 1 It can be seen that the manganese and iron elements in the manganese iron oxide obtained in Example 1 are mainly divalent. Figure 2 It can be seen that the manganese iron oxide obtained in Example 1 is in an agglomerated state, and the diameter of the primary particles is about 200-300 nm.

[0142] Figure 3 , Figure 4 They are the XRD spectrum and SEM image of the lithium manganese iron phosphate positive electrode material obtained in Example 1.

[0143] Figure 3 Compared with the lithium manganese iron phosphate standard card, there are fewer impurity peaks, which shows that the positive electrode material obtained in Example 1 has fewer impurities. Figure 4 It can be seen that the particles of the positive electrode material obtained in Example 1 are uniform, and the primary particle size is about 50 nm.

[0144] Figure 5 This is a SEM image of the lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1. It can be seen that the particles of the positive electrode material obtained in Comparative Example 1 are uneven, the sphericity is poor, and the primary particle size is about 200-300nm.

[0145] Test Example 2 By EDS line scanning, the phosphorus element signal intensity at different positions in the lithium manganese iron phosphate positive electrode material obtained in the above embodiment and comparative example was obtained, and the average value, standard deviation and coefficient of variation of the phosphorus element signal intensity were calculated, as shown in Table 1.

[0146] Figure 6 This is the EDS line scan of the phosphorus element in the lithium iron phosphate positive electrode material obtained in Example 1. It can be seen that the distribution uniformity of the phosphorus element is good.

[0147] Figure 7 This is the EDS line scan of the phosphorus element in the lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1. It can be seen that the distribution uniformity of the phosphorus element is poor.

[0148] Table 1

[0149] It can be seen from the results in Table 1 that the phosphorus element is more evenly distributed in the lithium manganese iron phosphate positive electrode material provided by the present invention.

[0150] Test Example 3 The positive electrode materials obtained in the above examples and comparative examples were mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 95:5:5 and coated on aluminum foil as the positive electrode; a lithium sheet was used as the counter electrode, and 1.2 mol / L LiPF 6 (Lithium hexafluorophosphate) was dissolved in EC (ethylene carbonate): PC (propylene carbonate): EMC (ethyl methyl carbonate) in a volume ratio of 1:1:1 as the electrolyte to make a CR2016 button battery.

[0151] The battery's 0.2C and 0.5C charge and discharge specific capacities were measured using the constant current-constant voltage charge and constant current discharge methods. The constant current was based on the selected rate, the constant current charge cutoff voltage was 4.4V, the constant voltage charge cutoff current was 1 / 10 of the constant current, and the discharge cutoff voltage was 2.5V. The results are shown in Table 2.

[0152] Table 2

[0153] It can be seen from the results in Table 2 that the battery made of the lithium manganese iron phosphate positive electrode material provided by the present invention has higher charge specific capacity and discharge specific capacity.

[0154] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium manganese iron phosphate positive electrode material, characterized in that: The expression of the positive electrode material is Li i (Fe x M y Mn z )PO4 / C; Among them, 0.15≤x≤0.45, 0 <y≤0.03,0.52≤z≤0.85,0.98≤i≤1.05; M is selected from at least one of Mg, Ti, V, Ni, Zn, Cu, Zr and Nb; The coefficient of variation of the phosphorus content in the positive electrode material is ≤0.

045.

2. The positive electrode material according to claim 1, characterized in that 0.15≤x≤0.35,0 <y≤0.01,0.64≤z≤0.85,1≤i≤1.02; Preferably, M is selected from at least one of Mg, Ti, Ni and Zn; Preferably, the coefficient of variation of the phosphorus content in the positive electrode material is ≤0.

035.

3. The positive electrode material according to claim 1 or 2, characterized in that In the positive electrode material, the carbon content is 1.4-2.5wt%; Preferably, the median particle size of the positive electrode material is 50-600 nm.

4. A method for preparing the positive electrode material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) in the presence of a first solvent, a manganese source, an iron source and an M source are mixed to obtain a mixed solution, and then mixed with oxalic acid and / or oxalate to separate a precipitate; (2) subjecting the precipitate to a first heat treatment under a protective atmosphere to obtain manganese iron oxide doped with the M element; (3) in the presence of a second non-aqueous solvent, mixing the manganese iron oxide with a lithium source, a phosphorus source and a carbon source to obtain a slurry, and grinding and drying the slurry to obtain a positive electrode material precursor; (4) Under a protective atmosphere, subjecting the cathode material precursor to a second heat treatment to obtain a lithium manganese iron phosphate cathode material.

5. The method according to claim 4, characterized in that The manganese source is selected from at least one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate; Preferably, the iron source is selected from at least one of ferrous sulfate, ferrous chloride and ferrous acetate; Preferably, the M source is selected from soluble salts of M; Preferably, the total concentration of metal ions in the mixed solution is 0.2-2 mol / L; Preferably, the mixed solution further comprises an antioxidant.

6. The method according to claim 4 or 5, characterized in that: The temperature of the first heat treatment is 500-700° C., and the time is 5-12 hours.

7. The method according to any one of claims 4 to 6, characterized in that: The lithium source is selected from at least one of lithium oxalate, lithium hydroxide, lithium carbonate, lithium acetate, and lithium dihydrogen phosphate; Preferably, the phosphorus source is selected from at least one of ammonium dihydrogen phosphate, phosphoric acid and lithium dihydrogen phosphate; Preferably, the carbon source is selected from at least one of glucose, galactose, lactose, sucrose, caramel, phenolic resin, polyethylene glycol and polyvinyl alcohol; Preferably, the first solvent is water; Preferably, the second non-aqueous solvent is N-methylpyrrolidone and / or anhydrous ethanol.

8. The method according to any one of claims 4 to 7, characterized in that: In step (1), the molar ratio of the manganese source, the iron source and the M source, calculated as metal elements, satisfies n(Mn):n(Fe):n(M)=1-1.2:0.4-1:0.015-0.045; And / or, in step (3), the molar ratio of the manganese iron oxide to the lithium source, the phosphorus source and the carbon source, calculated on the basis of metal elements, phosphorus elements and carbon elements, satisfies n(Li):n(Mn+Fe):n(P):n(C)=0.98-1.05:0.96-1:0.98-1.05:0.7-1.

3.

9. The method according to any one of claims 4 to 8, characterized in that: The solid content of the slurry is 20-70wt%; Preferably, the median particle size of the positive electrode material precursor is 100-200 nm.

10. The method according to any one of claims 4 to 9, characterized in that: The temperature of the second heat treatment is 220-800°C and the time is 4-12h; Preferably, the second heat treatment adopts a programmed temperature method: (1) Raise the temperature to 220-350℃ at a rate of 1-5℃ / min and keep warm for 2-3h; (2) Continue heating to 450-650℃ at a rate of 1.5-2.5℃ / min and keep warm for 4-5h; (3) Continue to increase the temperature to 650-800℃ at a rate of 1-1.5℃ / min and keep it at this temperature for 7-12h.

11. Use of the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the method according to any one of claims 4 to 10 in a battery.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN117623263A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN118103323A

  • Method for determining element content by using energy dispersive X-ray spectrometer

    CN118671116A

  • Preparation method of lithium manganese iron phosphate, positive electrode material and lithium ion battery

    CN119018869A

  • Negative electrode for lithium ion secondary battery

    JP2017111958A